Performance of air-cathode microbial fuel cell with wood charcoal as electrodes - Chai, Li Fen; Chai, Lay Ching; Napis, Suhaimi; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Local wood charcoal was used as the main component of the electrodes of an air-cathode microbial fuel cell (air-cathode MFC) in current study. The air cathode was build with fnely milled charcoal powder and cement plaster as binder; while anode was made up of a packed bed of charcoal granules. Mangrove estuary brackish water was inoculated in the anodic chamber as the fuel and a source of exoelectrogens. The constructed fuel cell was monitored by measuring the potential over time. The MFC generated a stable power density at 33mW/m2(0.5V) under a load of 200Ω after 72 hours of operation. An open circuit voltage (OCV) of 0.7mV was obtained after 15 hours operating under open circuit. The result of power generation by the constructed fuel cell indicating that wood charcoal could be used as electrode in an MFC and that brackish water contained potential exoelectrogens. However, further investigation and modifcation is required to increase the performance of the fuel cell.